Sosialisasi Penggunaan Antibiotik Yang Rasional Pada Pengunjung MTQ Kalsel 2023 - Hasniah, Hasniah; Su’aida, Nily; Soemarie, Yulistia Budianti; Erlianti, Karina (Prisani Cendekia, 2024)
Infectious diseases are one of the many health problems that occur in society, especially in Indonesia. The drugs commonly prescribed by doctors for the general public to overcome this problem are antibiotics. Antibiotics are drugs used by health to inhibit, kill or treat bacterial infections. However, the use of antibiotics is often misused, such as using antibiotics without a doctor's prescription, not finishing antibiotics, not using according to dosage, to treatment that should not require antibiotics. This poses a risk of antibiotic resistance. One of the factors causing this is the lack of education to the public regarding the use of drugs, especially antibiotics. The target of this activity is the people of South Kalimantan, precisely to the visitors of MTQ South Kalimantan 2023 where not a few of these people understand the use of antibiotics. This activity was carried out with the hope of educating the public about the use of good and correct antibiotics so as to prevent the development of antibiotic resistance. Based on the results of these activities, the people of South Kalimantan, namely visitors to MTQ South Kalimantan 2023, have received information on how to use antibiotics properly, correctly and rationally.